Menakar Tingkat Skeptisme Wajib Pajak Usaha Mikro Kecil dan Menengah - Rochman, Muhammad Fuyudlur; Surepno, Surepno (IAIN Kudus, 2023)
This study aims to identify the skepticism behavior of taxpayers that indicate tax compliance. This study uses the qualitative method of field research with interview as a research instrument. The case study is the taxpayers in Jepangpakis, with KPP Pratama Kudus, Jepang Pakis Government, and the taxpayers as research subject. The analysis research identifies that skepticism behavior of the taxpayers has different doses. The identify tells at least three different skepticism types, that is not-skeptic, medium skeptic, and quite serious skepticism. The abundance of the skepticism shows the connection with Tax compliance Theory by Alligham and Sandmo. Even though there is a lot of skepticism, there is no indication of low taxpayers’ compliance because of taxpayer’s intentions. That case shows the connection with Theory Planned Behavior (TPB) by Ajzen.